Seasonal and ENSO Influences on the Stable Isotopic Composition of Galápagos Precipitation. Issue 1 (13th January 2018) - Martin, N. J.; Conroy, J. L.; Noone, D.; Cobb, K. M.; Konecky, B. L.; Rea, S.
Abstract: The origin of stable isotopic variability in precipitation over time and space is critical to the interpretation of stable isotope‐based paleoclimate proxies. In the eastern equatorial Pacific, modern stable isotope measurements in precipitation (δ 18 Op and δDp ) are sparse and largely unevaluated in the literature, although insights from such analyses would benefit the interpretations of several regional isotope‐based paleoclimate records. Here we present a new 3.5 year record of daily‐resolved δ 18 Op and δDp from Santa Cruz, Galápagos. With a prior 13 year record of monthly δ 18 Op and δDp from the island, these new data reveal controls on the stable isotopic composition of regional precipitation on event to interannual time scales. Overall, we find Galápagos δ 18 Op is significantly correlated with precipitation amount on daily and monthly time scales. The majority of Galápagos rain events are drizzle, or garúa, derived from local marine boundary layer vapor, with corresponding high δ 18 Op values due to the local source and increased evaporation and equilibration of smaller drops with boundary layer vapor. On monthly time scales, only precipitation in very strong, warm season El Niño months has substantially lower δ 18 Op values, as the sea surface temperature threshold for deep convection (28°C) is only surpassed at these times. The 2015/2016 El Niño event did not produce strong precipitation or δ 18 Op anomalies due to the short period of warm SST anomalies, which did not extend into the peak of the warm season. Eastern Pacific proxy isotope records may be biased toward periods of high rainfall during strong to very strong El Niño events. Key Points: The amount effect in the Galápagos is manifested on daily and monthly time scales Rare, low δ 18 O rainfall values associated with deep convection during very strong El Niño events The 2015/2016 El Niño did not produce large precipitation or δ 18 O anomalies in the Galápagos